Event-related potential evidence of impaired proactive control in individuals with subthreshold depression - Wang, Zhijun; Hu, Jinsheng; Qiang, Qi; Liu, Zhihong; Yang, Qingshuo (Frontiers in Psychiatry, 2025)
Objective and rationaleCognitive control deficits are considered as central features of cognitive impairments in depression. The dual mechanisms of control (DMC)—proactive and reactive control—can further elucidate the nature of these deficits. However, evidence regarding proactive control in mild depression remains uncertain. This study investigated alterations of DMC and their related neural correlates in subthreshold depression (SD).MethodParticipants with SD were identified through a mental health screening and assigned to the SD group (n = 27), while healthy controls (HC) without depressive symptoms were recruited as the control group (n = 28). All participants completed the AX-Continuous Performance Task while measuring behavioral (reaction time and accuracy) and electrophysiological responses (cue-P3 and probe-N2/P3). The primary outcome focused on the alteration of proactive control in individuals with SD, assessed through group differences in BX performance and the cue-P3 component. Secondary outcomes encompassed AY trial performance and probe-N2/P3 components, indexing reactive control alteration in individuals with SD.ResultsSlower responses in BX and BY trials were observed for the SD relative to the HC group, indicating the impairment of context processing in individuals with SD. Event-related potential (ERP) results showed that cue-P3 components were less positive for the SD group relative to the HC group, indicating reduced cue utilization and attentional allocation to the cue in individuals with SD. Moreover, the positive correlation between the probe-N2 component and Beck Depression Inventory (BDI) scores implies that individuals with SD may rely more on reactive control.ConclusionThese findings suggest proactive control deficits in individuals with SD, as evidenced by diminished attentional allocation to the cue and inefficient cue utilization.